2006
DOI: 10.1111/j.1540-8191.2006.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Fascicular Conduction Disturbances After Coronary Artery Bypass Surgery: A Review With a Meta-Analysis of Their Long-term Significance

Abstract: Fascicular conduction abnormalities are frequently reported following adult cardiac surgery, but their pathogenesis and long-term outcomes remain unclear. In this article, we review the epidemiological features, pathogenesis, diagnosis, and management, and the short-term and long-term significance of fascicular conduction abnormalities following coronary artery bypass graft (CABG) surgery, based on data from 30 studies. Conduction disturbances have an incidence of 3.4% to 55.8% after CABG surgery, the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
6
0
3
Order By: Relevance
“…Previous studies have reported an incidence of conduction disturbances (CD) after CABG that varies from 18 to 55% of cases [ 1 - 6 ] , with the right bundle branch block being the most common [ 4 ] . Atrioventricular block (AVB) is one of these conduction disturbances and its incidence ranges from 0.5 to 16% [ 3 , 5 - 9 ] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported an incidence of conduction disturbances (CD) after CABG that varies from 18 to 55% of cases [ 1 - 6 ] , with the right bundle branch block being the most common [ 4 ] . Atrioventricular block (AVB) is one of these conduction disturbances and its incidence ranges from 0.5 to 16% [ 3 , 5 - 9 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of AVB seems to be multifactorial. The patient's age (>60 years), hypertension, number of revascularized vessels, aortic clamping time, total time of CPB, use of digitalis and beta-blockers, type of cardioplegia and previously existing left bundle branch block may be related to its appearance [ 1 - 4 , 8 , 9 , 13 , 14 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to traditional peptides, peptidomimetics have great proteolytic and metabolic stability and are believed to be less immunogenic, also with an enhanced bioavailability (Patch et al 2002;Goodman et al 2007;Wu et al 2008). The development of peptidomimetics to disrupt MDM2/p53 has led to a diverse set of oligomers such as -peptides (Seebach et al 1996;Cheng et al 2001;Kritzer et al 2005), -and -peptides (Arndt et al 2004;Trabocchi et al 2005;Kumbhani et al 2006), / -peptides (Horne et al 2008;Horne et al 2009), azapeptides (Graybill et al 1992;Lee et al 2002), -aminoxy-peptides (Li et al 2008), sugar-based peptides (Risseeuw et al 2007;Tuwalska et al 2008), peptoids (Simon et al 1992), oligoureas (Boeijen et al 2001;Violette et al 2005), polyamides (Dervan 1986), and phenylene ethynylenes (Nelson et al 1997), etc. Nonetheless, the development of peptidomimetics is far less straightforward, with the major limit lying in the availability of framework (Goodman et al 2007).…”
Section: Introductionmentioning
confidence: 99%